THE BREEDING OF PIGS, AS A WAY TO INCREASE THEIR FATTENING AND MEAT CHARACTERISTICS - Горобець, В. О. (Scientific Progress & Innovations, 2015)
The article presents the results of the evaluation of pigs of foreign origin and crownest of fattening and meat traits with determining of the best combinations of parental genotypes to obtain the effect of heterosis in the descendants. Research has shown that a hybrid young stock had the highest growth rate during feeding, who was obtained by crossing dohorty sows (large white of French origin x Duroc of German origin) with grunts of Pietrain breed of English origin. The largest declines of the young stock’s backfat thickness at 6-7 thoracic vertebrae and increase the mass of the posterior third of the side will ensure three times Pietrain boars’ cross breeding of English origin at the final stage. Purebred breeding of pigs of large white breed does not promote the fattening and meat traits in young stock, even for the unification of their genotype heredity animals of French, German and English origin. The profitability of fattening of young pigs in the conditions of modern industrial production should be based on associations of species, particularly when animals of foreign origin are used.